PENGARUH EDUKASI DAN LITERASI KEUANGAN DIGITAL TERHADAP MINAT INVESTASI JANGKA PANJANG GENERASI Z PENGGUNA FINTECH - Mahanani, Rima Nur; Hirawati, Heni; Sijabat, Yacobo P. (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The development of financial technology (fintech) has transformed the way Generation Z manages their finances. Despite improved access to financial services, interest in long-term investment remains relatively low among this demographic. This study aims to examine the extent to which financial education and digital financial literacy influence Generation Z's interest in long-term investment. A quantitative approach with a descriptive-correlational research design was employed. Data were collected through a survey of 69 university students aged 18–27 in the Yogyakarta region who had prior experience using fintech services. Data analysis was conducted using Microsoft Excel. The findings indicate that financial education has a strong and positive correlation with long-term investment interest, while digital financial literacy also shows a positive correlation. These results suggest that decisions to invest in the long term are significantly influenced by an individual’s understanding and ability to utilize digital financial services effectively.